adır- as a Word Family in Old Turkic and the Concept of Spli<ing - Üstüner, Ahat; Aka, Murat (Hacettepe University, 2024)
Word families point to very different conceptual domains depending on the conceptual relationships they contain. The verb adır-, which has an important place in Old Turkic in terms of frequency value, forms a very large word family group together with its derivatives. The word families formed by these words have acquired a wide variety of mental, political, social and individual meanings other than their physical meanings in different cultural circles of the old Turkic wriAen language. These meanings come to the fore especially through metaphors and metonymies and in some cases involve a further process of abstraction leading to grammaticalisation. According to cognitive linguistics, relations between different domains are considered as metaphor, and relations within the same domain are considered as metonymy. While the process of metaphorization is considered as a mapping from the source domain to the target domain, metonymy is accepted as the process of mental access to another concept within the same domain with reference interest. In this study, within the framework of conceptual metaphor and metonymy theory, the metaphor and metonymy processes of the words derived from the root *adı-/*ad- in Old Turkic will be analysed from the perspective of cognitive semantics. © 2024 Hacettepe University. All rights reserved.
ESKİ TÜRKÇEDE SÖZCÜK AİLESİ OLARAK adır- VE AYRILMA KAVRAMI
Keywords: adır-; Metaphor; Metonymy; Old Turkic; SpliAing; Word Family